2017
DOI: 10.1016/j.bbr.2016.08.039
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil chemotherapy upregulates cytokines and alters hippocampal dendritic complexity in aged mice

Abstract: 5-fluorouracil (5-Fu) is commonly used chemotherapy drug, but it can lead to the impairment of cognitive function. The pathogenesis of this injury is unknown but may involve modifications to dendritic structure and/or alterations in dendritic spine density and morphology. Dendritic spines are sites of excitatory synaptic transmission and changes in spine structure and dendrite morphology are thought to represent a morphological correlate of altered brain functions associated with hippocampal dependent learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 52 publications
(63 reference statements)
2
45
0
4
Order By: Relevance
“…In this study, mice were administered intraperitoneal injections of 5‐Fu, brains were collected, and Golgi staining was performed. Analogous to our results with thioTEPA, 5‐Fu significantly decreased dendritic branching and complexity (Groves et al, ). Cisplatin, another chemotherapy drug, also contributes to cognitive decline.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, mice were administered intraperitoneal injections of 5‐Fu, brains were collected, and Golgi staining was performed. Analogous to our results with thioTEPA, 5‐Fu significantly decreased dendritic branching and complexity (Groves et al, ). Cisplatin, another chemotherapy drug, also contributes to cognitive decline.…”
Section: Discussionsupporting
confidence: 92%
“…We found significantly lower levels of IL‐2, IL‐3, IL‐5, and GM‐CSF in thioTEPA‐treated animals compared to controls. However, previous studies generally observed an increase in cytokines during cognitive decline (Cheung et al, ; Groves et al, ; Lyons et al, ; Wilson, Finch, & Cohen, ). Because our data indicate a decrease in proinflammatory cytokines in thioTEPA‐treated mice, cognition should have been spared.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Specifically, Thiotepa administration in adult male mice caused deficits in short-term memory and in spatial memory retention [22]. 5-FU administrations compromised the structure of neurons in the hippocampus as seen by decreased dendritic length, complexity, and spine density [23]. Seigers et al showed that administration of cyclophosphamide or doxorubicin in adult male mice resulted in deficits in novel location recognition, a hippocampal dependent memory task.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several animal studies have revealed an important role for neuroinflammation in terms of dendritic spine structure. Increased cytokine levels inhibited the maintenance of dendritic spines either directly or indirectly, impairing hippocampus-dependent behaviors [ 22 23 ]. However, other studies suggested that hippocampal dysfunction and neuroinflammation were not linked.…”
Section: Introductionmentioning
confidence: 99%